2013
DOI: 10.1007/s10695-013-9884-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in digestive enzyme activities during larval development of leopard grouper (Mycteroperca rosacea)

Abstract: The leopard grouper is an endemic species of the Mexican Pacific with an important commercial fishery and good aquaculture potential. In order to assess the digestive capacity of this species during the larval period and aid in the formulation of adequate weaning diets, this study aimed to characterize the ontogeny of digestive enzymes during development of the digestive system. Digestive enzymes trypsin, chymotrypsin, acid protease, leucine-alanine peptidase, alkaline phosphatase, aminopeptidase N, lipase, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
5
25
0
1
Order By: Relevance
“…In the present study, the alkaline phosphatase specific activity of Chinese loach showed abrupt increase between 10 and 20 DAH, indicating the rapid development and/or formation of brush border enterocyte (Moyano et al 1996;Ribeiro et al 1999;Kvåle et al 2007) and an important development of the intestinal mucosa in terms of villi size and number (Pradhan et al 2013). Our results are in agreement with many other studies on the digestive physiology of fish larvae that reported an increase in intestinal brush border enzymes around the first weeks of their life stage (Babaei et al 2011;López-Ramírez et al 2011;Uscanga-Martínez et al 2011), indicating the onset of juvenile-like digestive mode (Ribeiro et al 1999;Martínez-Lagos et al 2014). The decrease in alkaline phosphatase specific activity was observed after 20 DAH as observed in yellowtail kingfish (Seriola lalandi) (Chen et al 2006), Mayan cichlid (López-Ramírez et al 2011) and butter catfish (Pradhan et al 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the alkaline phosphatase specific activity of Chinese loach showed abrupt increase between 10 and 20 DAH, indicating the rapid development and/or formation of brush border enterocyte (Moyano et al 1996;Ribeiro et al 1999;Kvåle et al 2007) and an important development of the intestinal mucosa in terms of villi size and number (Pradhan et al 2013). Our results are in agreement with many other studies on the digestive physiology of fish larvae that reported an increase in intestinal brush border enzymes around the first weeks of their life stage (Babaei et al 2011;López-Ramírez et al 2011;Uscanga-Martínez et al 2011), indicating the onset of juvenile-like digestive mode (Ribeiro et al 1999;Martínez-Lagos et al 2014). The decrease in alkaline phosphatase specific activity was observed after 20 DAH as observed in yellowtail kingfish (Seriola lalandi) (Chen et al 2006), Mayan cichlid (López-Ramírez et al 2011) and butter catfish (Pradhan et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Both amylase and lipase specific activities were detected as early as 1 DAH, suggesting that these enzymes were also genetically pre-programmed as reported in some other fish species (Cuvier-Péres and Lazo et al 2007;Martínez-Lagos et al 2014;Ma et al 2014). The amylase specific activity around 5 DAH was low coincided with the initial feeding, suggesting the poor ability of Chinese loach to utilize carbohydrates at mouth opening (4 DAH).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Wild mature individuals were induced to spawn with HCG producing >40,000 eggs/female (Gracia-López et al, 2004a) and hormonal induction on captive fish with HCG and LHRHa was successful producing over 2×10 6 eggs and fertilization rate of 62% (Kiewek-Martínez, 2004;. Embryonic development and egg and larval morphology and larval enzyme activity until the first feeding were described (GraciaLópez et al, 2004a;Martínez-Lagos & Gracia-López, 2009;Martínez-Lagos et al, 2014) and the effects of temperature and salinity on eggs and larvae also were studied (Gracia-López et al, 2004b). More than 1.7×10 6 eggs and 1.2×10 6 newly hatched larvae were achieved with a survival rate of 2.66% (Gracia-López et al, 2005).…”
Section: Introductionmentioning
confidence: 99%